Satellite observations reveal decreasing soil erosion in Northeast Inner Mongolia, China, over the past four decades - Jiang, Wei; Pang, Zhiguo; Lv, Juan; Ju, Hongrun; Li, Lin; Fu, June (Frontiers in Earth Science, 2022)
Knowledge about the soil erosion change pattern in Northeast Inner Mongolia is essential for ecological security and sustainable development. Multisource satellite remote sensing with auxiliary data, including meteorology, land use, vegetation coverage and digital elevation, were collected to establish a distributed soil erosion model to quantify the soil erosion intensity in Northeast Inner Mongolia. The results showed that soil erosion in Northeast Inner Mongolia, China, decreased by 100,654 km2 from 1978 to 2018. The area change rates of the mild, moderate, strong, intensive and severe soil erosion intensities were -48.91%, -41.41%, 32.63%, -91.15% and -91.14%, respectively. The decrease in soil erosion was mainly located in the Songliao Plain sand prevention farmland protection zone. Our findings from satellite observations provide information about the soil erosion intensity and spatial distribution required for policy-making and the management of soil erosion prevention in Northeast Inner Mongolia.